NEW LACANIAN COMMUNISM - Alfaro Vargas, Roy (2014)
This article analyzes, in the context of the current systemic and financial crisis and thedeepening of neoliberal policies, the proposal of several thinkers (Bosteels, Dean, Badiou yŽižek) in relation to the idea of a communism linked to the Lacanian real. It is then set upthat this new Lacanian communism evades the problems derived from the current crisisand from the resulting exacerbation of neoliberalism, and therefore it goes away from theMarxism with which it could be associated. In brief, the new Lacanian communism is anew philosophical idealism, which denies the anti-establishment political action and thesocial change.